A measure of authorship by publications. (19th November 2019) - Mukherjee, Conan; Basu, Ranojoy; Alam, Aftab
Abstract : Measuring publication success of a researcher is a complicated task as publications are often co‐authored by multiple authors, and so, it requires comparison of solo publications with joint publications. In this paper, like Price (1981), we argue for an egalitarian perspective in accomplishing this task. More specifically, we justify the need for an ethical perspective in quantifying academic author by identifying certain ethical difficulties of some popular contemporary indices used for this purpose. And then we show that for any given dataset of research papers, the unique method satisfying the ethical notions of identity independence and performance invariance must be the egaliatarian E ‐index proposed by Bose, Pal, and Sappington (2010) and Price (1981). In our setting, this egalitarian method divides authorship of joint projects equally among authors and sums across all publications of each author.